Clinical and biochemical profile of polycystic ovarian syndrome patients attending a tertiary care hospital - Dhakal, Sarita; Yadav, Naval Kishor; Poudel, Sheshkanta; Kumari Rana, Til; Shah, Binita (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: Polycystic ovarian syndrome (PCOS) is the most common cause of infertility in females, affecting between 6 to 22% of women worldwide. This study aimed to study clinical and biochemical profile in patients with PCOS. Methods: A descriptive cross-sectional study was carried out. The patients who visited to Gynecology and Obstetrics department, College of Medical Sciences, Bharatpur, Chitwan with complaints of unable to conceive, irregular cycle and abnormal bleeding and diagnosed with polycystic ovarian syndrome were included in this study. Data was analyzed by using SPSS version 23.0. Data was analyzed by using descriptive statistical tolls. Results: Among the total 100 participants, 29%, had increased luteinizing hormones (LH), 2% had increased follicular stimulating hormone (FSH) level. The ratio of LH/ FSH is >2 in 73% of the participants. Majority (65.0%) of them were in the age group 21 to 30 years. The mean±SD of age was 23.41±4.62 years. Among the participants 56% were pre-obese. The prevalence of hypothyroidism among the participants was 18.0% and serum prolactin level was increased in 17%. There were no statistically significance between age, marital status, thyroid status, serum prolactin, with LH, and FSH. However, body mass index (BMI) was statistically significant with FSH negatively (p=-0.229). Conclusions: In this study, most of the participants were pre-obese, and affects the age group between 21 to 30 years. BMI was statistically significant with FSH. However, other parameters were statistically insignificant with LH and FSH levels.